2017
DOI: 10.1111/crj.12649
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3polymorphisms in interstitial lung disease among Chinese Han population: A genetic association study

Abstract: FOXP3 polymorphisms may be important markers to determine susceptibility to IIP or CTP-ILD in Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…The rs2280883 SNP is also linked to an increased risk of Graves' disease (Tan et al, 2021). Additionally, the association of the TC genotype of Foxp 3 rs2280883 was found with the risk of connective-tissue-disease-associated ILD [23]. Findings in other studies, together with the Foxp 3 -polymorphism-associated genetic effect on the risk of SLE identified in this study, confirm our hypothesis that Foxp 3 polymorphisms might be a proper candidate for use in autoimmune disease screening, including for SLE.…”
Section: Discussionmentioning
confidence: 96%
“…The rs2280883 SNP is also linked to an increased risk of Graves' disease (Tan et al, 2021). Additionally, the association of the TC genotype of Foxp 3 rs2280883 was found with the risk of connective-tissue-disease-associated ILD [23]. Findings in other studies, together with the Foxp 3 -polymorphism-associated genetic effect on the risk of SLE identified in this study, confirm our hypothesis that Foxp 3 polymorphisms might be a proper candidate for use in autoimmune disease screening, including for SLE.…”
Section: Discussionmentioning
confidence: 96%
“…In the current study, a total of four FOXP3 SNPs rs3761547, rs3761548, rs3761549, and rs2232365 were selected based on the International HapMap Project database [24]. The FOXP3 rs3761547 was selected because the FOXP3 rs3761547 polymorphisms was suggested as a male-specific risk factor in multiple sclerosis [25], or important markers to determine susceptibility and risk of diseases such as Crohn's disease [26] and interstitial lung disease (ILD) [27]. The rs3761548 was selected because it was suggested that the FOXP3 rs3761548 SNPs could affect the susceptibility to gastric adenocarcinoma (GA) and the serum IL-35, IL-10, and TGF-β concentrations [20], and the rs3761548 polymorphism of FOXP3 gene may provide as a risk factor in the development of breast cancer (BC) [28].…”
Section: Selection Of Foxp3 Snpsmentioning
confidence: 99%
“…Recently, prospective data were collected over 2 years in the north of India using the American Thoracic Society/European Respiratory Society (ATS/ERS) consensus statement on idiopathic interstitial pneumonias (IIP) as a benchmark and sarcoidosis was the most frequent diagnosis of ILD. Investigations about the role of both genetic and environmental factors have also been conducted and showed that FOXP3 polymorphisms might determine the susceptibility IIP or CTD‐ILD in Chinese Han population and African‐American race refers to a younger age at ILD diagnosis and a better survival . A new cluster analysis among adults with various chronic ILD has been conducted, and four distinct clinical phenotypes were identified, allowing a better prediction of clinical outcomes than the current ILD diagnostic criteria.…”
Section: Interstitial Lung Diseasementioning
confidence: 99%